Ethnic identity features in convicted migrants with recidivist behavior: development of tolerance among convicted migrants to other ethnic groups - O. S. Dzhumabaev; M. V. Iontseva (Вестник университета)
By the end of adolescence, a person develops ethnic identity that affects their future destiny. The purpose of the study is to analyze formation of ethnic identity features in convicted migrants and development of tolerance among them. In the process of work theoretical research methods have been used. The presence of personal attitudes determines future actions that may be criminal. The increase in the number of convicted migrants who commit crimes repeatedly is characterized by criminalization degree presence, as well as personal and behavioral traits. Ethnic identity in this case has a cognitive component based on criminogenic for a certain benefit. The peculiarities of recidivism manifestation include existence of certain dependencies that link the increase in the severity and rate of crimes committed and increase in the number of convictions, which leads to an increase in recidivism as a result of an increase in crime. The development of tolerance among convicted migrants requires development and implementation of measures aimed at reducing aggression and accepting diversity of culture of other ethnic groups.